Nonlinear dynamics and seismic response of power transmission lines - El-Attar, Mohsen Mohamed (My University, 1997)
Electric power transmission lines have been traditionally designed for wind and ice loads. The earthquake load has not been considered in the analysis of transmission lines. During recent earthquakes, there have been indications of damage to transmission lines. Due to the complex nature of the problem, there is a lack of research work in the area of seismic analysis of transmission lines. The objective of this study is to evaluate the response of transmission lines to earthquake ground motion in order to evaluate the current design code methodology. The scope of this research program includes: (1) Modelling of different parts of the transmission line to analyze its seismic response, (2) comparison between the forces generated in the transmission tower members by wind, ice and earthquake loads, and (3) analyzing the probabilistic characteristics of the cable response to earthquake ground motion in order to establish a seismic design procedure for transmission lines. An intermediate span of a typical transmission line is chosen for the analysis. The tower members are modelled as truss elements. The cables are modelled by two node elements that retain their geometric nonlinearity. The dynamic characteristics of different components of the line (towers and cables) are determined in order to obtain a better understanding of the line behaviour. The in-plane and out-of-plane vibrations of the line are analyzed. The transmission line response to multiple support as well as uniform support excitations is evaluated. A closed form analytical solution for the cable vibration is carried out for a more detailed study of the cable nonlinear behaviour. It is concluded from the analysis that earthquake ground motion may cause substantial displacements and internal forces in the transmission line elements. The forces in transmission tower members due to the earthquake load may exceed those caused by the wind loads specified by the National Electrical Safety Code (NESC, 1993). Seismic ground motion may cause large displacement in the transmission line cables. This suggests that the cable motion during earthquakes should be included in the design of the line clearances to avoid having cables touch each other, which may cause power failure.
Keywords: Civil Engineering; Civil Engineering